Grace, reconciliation, concor d the death of Christ in Graeco-Roman metaphors - Breytenbach, Cilliers, 1954- (Novum Testamentum, Supplements, 2010)
How did the first Christians interpret the death of Christ? The answer lies within the earliest Christian documents, primarily within the Pauline letters. Before the users of a modern language could hope to come near an adequate description of what was expressed in these Greek texts of the first Christians, they have to deconstruct layers of later dogmatic interpretation. They need to keep to descriptive terminology reflecting the Greek of the sources and to trace the origin of the metaphoric language early Christians like Paul used. This volume sets out to construct some of the Jewish and Greco-Roman patterns of thought which were initially utilised to express the meaning of the death of Christ.